Sistik Food Business Opportunities in the Digital Age in the Fatayat Bungursari Environment - Sabiq Syahid Muslim; Shopi Guspiati (Communigate, 2025)
In the rapidly evolving digital era, the role and potential of the business sector are increasingly wide open, especially for groups interested in entrepreneurship. Amid the complexities of today’s economy, Fatayat women hold significant potential to become active and influential business players in the food industry. This study aims to identify and explore business opportunities in the digital era that can be introduced to Fatayat women through sistik food entrepreneurship as an attractive alternative. The research methods employed include surveys and structured interviews with a group of Fatayat women interested in engaging in the food business. Data were collected to assess their understanding of digital business potential, the challenges they might face, as well as their interest and readiness to run a sistik food business. The findings reveal that most respondents have limited understanding of digital business potential but show a high interest in learning and participating in sistik food entrepreneurship. Factors such as technological knowledge, initial capital, market access, and managerial skills are key considerations in starting this venture. By providing training, mentoring, and access to necessary resources, Fatayat women can become agents of change in leveraging digital technology to develop the sistik food business. This research contributes to identifying new business potential in the digital era while stimulating the interest and readiness of Fatayat women to engage in sustainable entrepreneurship.